(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In today‟s world the most difficult task is to make assessment of the need or purchasing patterns of the consumer due to the changes occurring in the way of shopping by the consumer. The customer has various options to make the purchase. Up to the last decade of this century there was prominence of the face to face purchase. That is to say customer visits the shop and purchases the goods which he like most and after bargaining he purchases the goods. This was the most preferred method of the shopping earlier. With the easy access to the internet, and the availability of the internet on each mobile and laptop, customer find it easy to make purchasing online i.e. to make purchasing electronically. This has generated the most powerful industry of the today‟s world called E-Commerce Industry. The easiness of making shopping on internet is most attractive feature of the E-Commerce shopping. By the single clicking thousands of the options are available to customer which was not available to him in direct market shopping. In the offline shopping number of available options are so limited that customer sometimes remained unsatisfied. This is not the case in E-Commerce shopping. This has enhanced the market size of every kind of the product including FMCG. With the rapid development of the technology and increasing easy and fast availability of the internet the customer base at E-Commerce platform is increasing. However this has also lead to a highest level of cut throat competition in the market and now a trader or service provider has to compete at the national level. This makes his survival though and it will not going to be easy for him to make a monopoly. He has to be advanced in everything of his efforts including updation of the product range, advancement of the technology and quality as well. This research is undertaken to evaluate the impact of the E-Commerce Industry on the buying behavior of the consumer by evaluating various factors such as consumer preference, age factor of the consumer, age of the consumer and like nature. This study will be helpful future researches of like nature.